قوّة الهجين والقدرة على الائتلاف لصفة الغلّة ومكوناتها في هجن نصف تبادلية من الذرة الصفراء (Zea mays L.). - خوري, بولص; قبيلي, صالح; مسعود, إيمان (Latakia University Journal -Biological Sciences Series, 2016)
نُفذَّ هذا البحث في قسم بحوث الذرة خلال الموسمين الزراعيين 2010 - 2011، بهدف تقدير القدرة العامة والخاصة على الائتلاف وكذلك قوّة الهجين، لصفات غلّة النبات الفردي، وارتفاع النبات، وعدد الصفوف بالعرنوس، وعدد الحبوب بالصف، ووزن الـ 100 حبّة، وارتفاع العرنوس, وطول وقطر العرنوس وصفة الإزهار المؤنث. لست سلالات نقيّة (مرباة ذاتيّاً) من الذرة الصفراء باستخدام التهجين نصف التبادلي وخلصت النتائج إلى ما يأتي: كان تباين السلالات والهجن عالي المعنويّة لكلِّ الصفات المدروسة وأظهرت القدرة العامّة والخاصّة على الائتلاف تبايناً معنويّاً لكلِّ الصفات عدا تباين القدرة الخاصّة على الائتلاف لصفة ارتفاع النبات وعدد الحبوب بالصف وارتفاع العرنوس مبيّناً ذلك مساهمة كلٍّ من الفعل الوراثي الإضافي واللاإضافي في وراثة معظم هذه الصفات. بينت نسبة تباين القدرة العامة على تباين القدرة الخاصة σ2GCA/σ2SCAسيطرة الفعل الوراثي الإضافي على وراثة كلٍّ من صفة ارتفاع النبات، وعدد الصفوف بالعرنوس، وعدد الحبوب بالصف، وارتفاع العرنوس، وطول العرنوس، بينما سيطر الفعل الوراثي اللاإضافي على وراثة كلٍّ من صفة غلّة النبات الفردي ووزن الـ 100 حبّة، والإزهار المؤنث، ومساهمة كلٍّ من الفعلين الوراثيين الإضافي واللاإضافي في وراثة صفة قطر العرنوس. أبدت جميع الهجن قوّة هجين إيجابية وعالية المعنوية قياساً لمتوسط الأبوين والأب الأفضل لجميع الصفات المدروسة. أبدت السلالتان CML.367 و CML.485 قدرة عامة جيدة على الائتلاف لصفة غلّة النبات الفردي. أظهرت ثلاثة هجن قدرة خاصة جيدة على الائتلاف لصفة غلّة النبات الفردي كان أفضلها الهجين (CML.373×CML.317). This study was carried out during growing seasons in 2010-2011 at the Maize Researches Department (G.C.S.A.R.) in Damascus. The study, using half diallel of crosses for six inbred lines of maize, aimed at estimating heterosis and combining ability components for grain yield per plant, plant height, number of rows per ear, number of kernel per row, weight of 100 kernels, ear height, ear length, ear diameter, and silking date. The major findings were: The inbred lines and hybrid percentage was highly significant. Inbred lines crosses, and the general (GCA) and specific (SCA) combining ability mean squares were significant for all traits except SCA mean squares for plant height and number of kernel per row, and ear height. The ratios of σ2GCA/σ2SCA showed that additive gene action was more dominant than non-additive gene action in controlling plant height, number of rows per ear, number of kernel per row, ear height and ear length, whereas non-additive gene action was more dominant than the additive one in grain yield per plant, the 100 kernel weight, and the silking date. On the other hand, the study indicated that the ear diameter trait was controlled by both additive and non-additive gene action. All heterosis percentage for all traits was highly significant compared with the average rate of parents and the better parent. GCA effects showed that the lines CML.367 and CML.485 were good combiners for grain yield per plant. SCA effects showed that three hybrids were the best F1 cross combinations such as ) CML.317 ×CML.373) for grain yield.